2020
DOI: 10.1177/1540796920927656
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Perceptions of Constraints Impacting the Development of Walking in Children with CHARGE Syndrome

Abstract: This study examined parents’ perceptions of constraints that impact the attainment of independent walking in children with CHARGE syndrome. This syndrome is a multifaceted syndrome including a degree of vision and hearing loss at birth. The Dynamic Systems Theory (DST) was used as an ecological lens to provide insight into the complexity of issues impacting independent walking from the parents’ perceptions. Semi-structured interviews were administrated to 23 parents of children with CHARGE syndrome to ascertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…A second aim of this study was to examine the relationship between home environment affordances with the age of onset of motor milestones in young children with CHARGE syndrome due to their delays in motor development [32]. Similar to prior research [18][19][20], the results of the present study found significant delays in the acquisition of motor milestones in the children with CHARGE syndrome, such as age of standing and independent walking occurring significantly later than their peers without disabilities. Interestingly, however, age of walking was associated with the number of toys in the home.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…A second aim of this study was to examine the relationship between home environment affordances with the age of onset of motor milestones in young children with CHARGE syndrome due to their delays in motor development [32]. Similar to prior research [18][19][20], the results of the present study found significant delays in the acquisition of motor milestones in the children with CHARGE syndrome, such as age of standing and independent walking occurring significantly later than their peers without disabilities. Interestingly, however, age of walking was associated with the number of toys in the home.…”
Section: Discussionsupporting
confidence: 79%
“…Motor milestones are early motor skills that follow a particular sequence from holding the head up to independent walking. Children with CHARGE syndrome walk an average of 25 months later than their sighted peers [19,20]. One reason for this late onset for independent walking is that children with CHARGE syndrome experience more balance issues compared to their peers without disabilities [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Haibach and Lieberman (2013) and Haibach-Beach et al (2020) have found that children with CHARGE syndrome have limited balance ability, which can directly affect performance on locomotor skills. Furthermore, balance was reported by parents of children with CHARGE syndrome as a rate limiter impeding their child’s ability to develop independent walking (Foster et al, 2020). Thus, it is not surprising that the current study found significant negative correlations between age at independent walking and locomotor performance for the children with CHARGE syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Children with CHARGE syndrome have additional barriers, such as a variety of medical complications, that often require frequent hospitalizations, multiple surgeries, and long recoveries, which can slow and even impede with natural motor development and educational programming (Hartshorne et al, 2011; Salem-Hartshorne & Jacob, 2005). Foster et al (2020) reported that parents of children with CHARGE syndrome perceived restricted environments, such as hospitals, and even medical equipment, as a cause for motor developmental delay in walking. Even when these children return from their medical leave, they are often excused from physical education for extended periods of time (Hilgenbrinck et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has found that children with CS are delayed in motor competence in comparison to their peers without disabilities (Haibach-Beach et al, 2019;Perreault et al, 2021), which often concerned parents. It has been well documented that children with CS already experience delayed walking (Foster et al, 2020;, balance deficits (Haibach et al, 2013;Haibach-Beach et al, 2020), and vestibular challenges (Möller, 2011), which can contribute to these delays in motor development. As such, children with CS have significantly lower locomotor, ball skills, and total skill scores compared to their peers without disabilities.…”
Section: Discussionmentioning
confidence: 99%